Konstantin Grcic : decisive design. - Ryan, Zoë, ....- (Chicago : Art Institute of Chicago, 2009)
The hip, functional, and versatile furniture and products of Konstantin Grcic-widely recognized as one of the most important designers working today-are transforming the landscape of contemporary design. This book accompanies the first exhibition in North America of Grcic's work, highlighting the innovative archetypes of form and concept that have marked his remarkable output since 2004. Grcic delights in creating fresh takes on familiar industrial objects, whether desks, chairs, benches, stools, a range of kitchen equipment, lamps, a set of salad servers, or Krups coffee makers. In his recent work, he has blended his characteristic simplicity and distinctiveness with the use of new technologies and materials-for example, a cantilevered stacking chair, Myto (2008), is made from a strong, fluid plastic typically used by the automotive industry.